2021
DOI: 10.1093/ve/veab032
|View full text |Cite
|
Sign up to set email alerts
|

Interannual dynamics, diversity and evolution of the virome in Sclerotinia sclerotiorum from a single crop field

Abstract: Mycovirus diversity is generally analyzed from isolates of fungal culture isolates at a single point in time as a snapshot. The stability of mycovirus composition within the same geographical location over time remains unclear. Not knowing how the population fluctuates in the field can be a source of unpredictability in the successful application of virocontrol. To better understand the changes over time, we monitored the interannual dynamics and abundance of mycoviruses infecting Sclerotinia sclerotiorum at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 66 publications
1
83
0
Order By: Relevance
“…However, jingmenviruses are phylogenetically clustered in a separate group that is distinctive from the genera of Flavivirus [49]. Recently, the novel narna-like viruses and virga-like mycovirus with segmented genomes have been found in Aspergillus species, S. sclerotiorum, and endomycorrhizal fungi, suggesting that mycovirus genome segmentation are more complex [5][6][7]. From PLOS PATHOGENS our present study, SsDFV3 has a tripartite genome, and was phylogenetically positioned into previously characterized unsegmented deltaflexiviruses group based on conserved RdRp domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, jingmenviruses are phylogenetically clustered in a separate group that is distinctive from the genera of Flavivirus [49]. Recently, the novel narna-like viruses and virga-like mycovirus with segmented genomes have been found in Aspergillus species, S. sclerotiorum, and endomycorrhizal fungi, suggesting that mycovirus genome segmentation are more complex [5][6][7]. From PLOS PATHOGENS our present study, SsDFV3 has a tripartite genome, and was phylogenetically positioned into previously characterized unsegmented deltaflexiviruses group based on conserved RdRp domain.…”
Section: Discussionmentioning
confidence: 99%
“…Three RNA segments (SsDFV3S1-S3) were recently detected in a previously characterized S. sclerotiorum strain SCH941 and its single protoplast isolate (S2B Fig). Moreover, seven of hundred S. sclerotiorum isolates isolated from a single crop field were also infected with this virus with the three fragments (S2C and S2D Fig) [5], which suggested that SsDFV3 could be widespread in S.…”
Section: A Deltaflexivirus Contains Three Rna Segments Derived From Its Unsegmented Relatives and Heterologous Virusesmentioning
confidence: 93%
See 2 more Smart Citations
“…A study to include multiple sites can be advantageous, especially if the disease in question is widespread and the pathogen is cosmopolitan. It would be interesting to monitor whether there is a correlation between the mycoviral read counts and the disease severities and yield intra-annually [ 30 ], since yield enhancement has been reported in a mycovirus that presents in fields of brassica spp. [ 16 ].…”
Section: Discussionmentioning
confidence: 99%